2020
DOI: 10.1038/s41598-020-69051-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-omics data revealed commonalities and differences between Rpv12- and Rpv3-mediated resistance in grapevine

Abstract: Plasmopara viticola is the causal agent of grapevine downy mildew (DM). DM resistant varieties deploy effector-triggered immunity (ETI) to inhibit pathogen growth, which is activated by major resistance loci, the most common of which are Rpv3 and Rpv12. We previously showed that a quick metabolome response lies behind the eti conferred by Rpv3 tiR-nB-LRR genes. Here we used a grape variety operating Rpv12-mediated eti, which is conferred by an independent locus containing cc-nB-LRR genes, to investigate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…There are some indications for the occurrence of a secondary defense mechanism. In V. riparia, a dramatic increase in JA was observed only at 48 hpi (Polesani et al, 2010) and in Rpv12 carriers, genes related to SA synthesis and signaling were only differentially expressed from 48 hpi (Chitarrini et al, 2020). Moreover, the first infection steps of Rpv3.1 + cultivars (Eisenmann et al, 2019) and Solaris (Busam et al, 1997;Boso and Kassemeyer, 2008) are essentially the same as in the susceptible V. vinifera, even though gene expression studies show that the defenses are induced at the first interaction between host cells and pathogen hyphae (Polesani et al, 2010;Eisenmann et al, 2019).…”
Section: Phytohormones Responses In Rpv31 Rpv10 and Rpv12mentioning
confidence: 96%
“…There are some indications for the occurrence of a secondary defense mechanism. In V. riparia, a dramatic increase in JA was observed only at 48 hpi (Polesani et al, 2010) and in Rpv12 carriers, genes related to SA synthesis and signaling were only differentially expressed from 48 hpi (Chitarrini et al, 2020). Moreover, the first infection steps of Rpv3.1 + cultivars (Eisenmann et al, 2019) and Solaris (Busam et al, 1997;Boso and Kassemeyer, 2008) are essentially the same as in the susceptible V. vinifera, even though gene expression studies show that the defenses are induced at the first interaction between host cells and pathogen hyphae (Polesani et al, 2010;Eisenmann et al, 2019).…”
Section: Phytohormones Responses In Rpv31 Rpv10 and Rpv12mentioning
confidence: 96%
“…The most popular omics utilizes bioinformatics to analyze fungal–metal interactions at a nucleotide and protein level, which can reveal novel genes and mutations. In genomics, the entirety of a genome is assessed and compared to others for similarities and differences that can contribute to an organism’s characteristics [ 302 , 303 ]. Transcriptomics relies on RNA sequencing to survey gene expression through fold-changes in transcripts and proteomics assess fold-change in subsequent proteins.…”
Section: Omics and Metal Homeostasismentioning
confidence: 99%
“…For example, Wang et al 28 showed that stilbene synthase ( VvSTS ) was induced earlier in DM-resistant M. rotundifolia than in susceptible V. vinifera tissues following DM inoculation, while the resveratrol O -methyltransferase ( ROMT ) gene was upregulated in only the resistant genotype. More recent studies with V. vinifera hybrids containing either the Rpv3 or Rpv10 resistance locus have also strongly suggested a role for stilbenes in DM resistance mediated by these loci 23 , 24 , 29 . Similarly, in Rpv12 -mediated DM resistance, trans-resveratrol was proposed to act as a signaling molecule in ROS formation and initiation of programmed cell death (PCD) triggered by a CC-NB-LRR gene product 24 .…”
Section: Introductionmentioning
confidence: 97%
“…More recent studies with V. vinifera hybrids containing either the Rpv3 or Rpv10 resistance locus have also strongly suggested a role for stilbenes in DM resistance mediated by these loci 23 , 24 , 29 . Similarly, in Rpv12 -mediated DM resistance, trans-resveratrol was proposed to act as a signaling molecule in ROS formation and initiation of programmed cell death (PCD) triggered by a CC-NB-LRR gene product 24 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation